Time on treatment with abiraterone and enzalutamide in the Patient-overview Prostate Cancer in The National Prostate Cancer Register of Sweden. (2nd December 2021) - Fallara, Giuseppe; Alverbratt, Charlotte; Garmo, Hans; Vikman, Hanna; Hjelm Eriksson, Marie; Lissbrant, Ingela Franck; Stattin, Pär
Abstract: Background: There are little and inconsistent data from clinical practice on time on treatment with the androgen receptor-targeted drugs (ART) abiraterone and enzalutamide in men with metastatic castration-resistant prostate cancer (mCRPC). We assessed time on treatment with ART and investigated predictors of time on treatment. Material and methods: Time on treatment with ART in men with mCRPC in the patient-overview prostate cancer (PPC), a subregister of the National Prostate Cancer Register (NPCR) of Sweden, was assessed by use of Kaplan–Meier plots and Cox regression. To assess the representativity of PPC for time on treatment, a comparison was made with all men in NPCR who had a filling for ART in the Prescribed Drug Registry. Results: 2038 men in PPC received ART between 2015 and 2019. Median time on treatment in chemo-naïve men was 10.8 (95% confidence interval 9.1–13.1) months for abiraterone and 14.1 (13.5–15.5) for enzalutamide. After the use of docetaxel, time on treatment was 8.2 (6.5–12.4) months for abiraterone and 11.1 (9.8–12.6) for enzalutamide. Predictors of a long time on treatment with ART were long duration of ADT prior to ART, low serum levels of PSA at start of ART, absence of visceral metastasis, good performance status, and no prior use of docetaxel. PPC captured 2522/6337 (40%) of all men in NPCR who had filled a prescription for ART. Based on fillings in the Prescribed Drug Registry, men in PPC had a slightly longer median time on treatment with ART compared to all men in NPCR, 9.6 (9.1–10.3) vs. 8.6 (6.3–9.1) months. Conclusions: Time on treatment in clinical practice was similar or shorter than that in published RCTs, due to older age, poorer performance status and more comorbidities.